Effect of Transformational Leaders and Work Motivation on Employee Performance: Case Study in East Java Provincial Government - Muhammad Irsyadul Ibad; Hafid Kholidi Hadi (CV ODIS, 2022)
This study aims to test and influence analysis of transformational leadership and work motivation on employee performance of the regional secretariat office of the province of east java, which is located on Jalan Pahlawan No 110 alun-alun contong, Bubutan District, Surabaya City, East Java (60174). . Data collection method using questionnaires, interviews and literature studies whose population was obtained from all employees whoo opened 51 employees. Data obtained by questionnaire technique through google form. Data wahre analyzed by simple regression with SPSS. The result shows that the first accepted hypothesis is that transformational leadership has a positive effect on employee performance, the second hypothesis is that work motivation has a positive effect on employee performance. The dominant influence is show in work motivation on employee performance.